2020
DOI: 10.1039/d0ra01470b
|View full text |Cite
|
Sign up to set email alerts
|

MOF-derived Bi2O3@C microrods as negative electrodes for advanced asymmetric supercapacitors

Abstract: Bi2O3 microrods with a carbon coat (Bi2O3@C) exhibit ultrahigh specific capacity (1378 C g−1 at 0.5 A g−1) and excellent cycling stability (93% retention at 4000 cycles) as negative electrodes for supercapacitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 38 publications
2
22
0
Order By: Relevance
“…It can be found that although the material is purely BiSe, as characterized by XRD, there are a small amount of Bi-O bonds in the material. 40,42 The peak at 58.4 eV corresponds to SeO x , which is due to partial oxidation in air. 77…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be found that although the material is purely BiSe, as characterized by XRD, there are a small amount of Bi-O bonds in the material. 40,42 The peak at 58.4 eV corresponds to SeO x , which is due to partial oxidation in air. 77…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Chavan et al reported Hematite α-Fe 2 O 3 thin films by spray pyrolysis from a non-aqueous medium, showing a specific capacitance of 451 F g −1 at 5 mV s −1 with a potential window ranging from −1.1 to 0.2 V. 41 Han et al prepared Bi 2 O 3 microrods with a carbon coat (Bi 2 O 3 @C) by a facile metalorganic framework (MOF)-derived strategy, which exhibited a high specific capacity of 1378 C g −1 at 0.5 A g −1 and excellent cycle life (93% after 4000 cycles). 42 Despite these achievements, these metal compounds usually suffer from unsatisfactory rate capability, low electronic conductivity or inferior stability, leading to the unsatisfactory electrochemical performance. Therefore, more perfect materials with improved electrical conductivity should be explored to present satisfactory electrochemical performance.…”
Section: Introductionsmentioning
confidence: 99%
“…The power density (P, W/kg) and energy density (E, Wh/ kg) of PEA-derived CNFs were calculated from the experimental GCD curves, according to the following equations: 56,57…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The power density ( P , W/kg) and energy density ( E , Wh/kg) of PEA-derived CNFs were calculated from the experimental GCD curves, according to the following equations: , where I is the applied current density, Δ V is the potential window, m is the mass of the electrode material, and t is the discharge time. The P and E values of PEA-derived CNFs at the current densities of 1–10 A/g were evaluated to be 69.2–27.8 Wh/kg and 1,000–10,000 W/kg, respectively, as can be seen in the Ragone plot of Figure D.…”
Section: Resultsmentioning
confidence: 99%
“…evaluated as 66.7-179.3 F g −1 (Figure 9C). In addition, the gravimetric power density (P, W kg −1 ) and energy density (E, Wh kg −1 ) of the symmetric capacitor based on HCNF7 electrodes could be calculated using the following equations: [22,61]…”
mentioning
confidence: 99%